2021
DOI: 10.21580/vjv10i29096
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Preferable Types of Teacher Humor in English Classes

Abstract: The current study aimed to explore what types of teacher humor EFL students prefer in their classes. The study was designed as a mixed-method approach, using questionnaires and semi-structured interviews to collect data in two different Vietnamese universities. One hundred fifty-eight university students responded to the survey, and eight out of them were recruited as the participants for the interviews. The study results revealed that the types of jokes (M=4.41), riddles (M=4.08), and language play (M=4.15) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…According to the data analysis, the study found that: (1) using humour stories effectively helps students' reading comprehension; and (2) using humour stories motivates students to develop reading comprehension. This is also supported by Thuy (2021) in a study conducted in Vietnam, it was found that the three most preferable forms of teacher humour were jokes, language play, and riddles. The finding also shows that visual humour in a form of writing enables teachers to enhance the learning experience for students.…”
Section: The Types Of Humour In Eltsupporting
confidence: 56%
“…According to the data analysis, the study found that: (1) using humour stories effectively helps students' reading comprehension; and (2) using humour stories motivates students to develop reading comprehension. This is also supported by Thuy (2021) in a study conducted in Vietnam, it was found that the three most preferable forms of teacher humour were jokes, language play, and riddles. The finding also shows that visual humour in a form of writing enables teachers to enhance the learning experience for students.…”
Section: The Types Of Humour In Eltsupporting
confidence: 56%